2008
DOI: 10.1007/s10295-008-0439-1
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Bacillus thuringiensis var. israelensis growth on high glucose concentrations

Abstract: The kinetic and general growth features of Bacillus thuringiensis var. israelensis were evaluated. Initial glucose concentration (S0) in fermentation media varied from 10 to 152 g/l. The results afforded to characterize four morphologically and physiologically well-defined culture phases, independent of S0 values: Phase I, vegetative growth; Phase II, transition to sporulation; Phase III, sporulation; and Phase IV, spores maturation and cell lysis. Important process parameters were also determined. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
1
18
0
2
Order By: Relevance
“…As can be observed (Table 1; Fig. 1), in neither case total glucose consumption took place during cellular growth (phases I and II), probably due to the depletion of yeast extract in fermentation broth, as previously demonstrated (Berbert-Molina et al 2008). The highest Y x/s value (0.53 g/g) was obtained with 50% DO.…”
Section: Resultssupporting
confidence: 55%
See 4 more Smart Citations
“…As can be observed (Table 1; Fig. 1), in neither case total glucose consumption took place during cellular growth (phases I and II), probably due to the depletion of yeast extract in fermentation broth, as previously demonstrated (Berbert-Molina et al 2008). The highest Y x/s value (0.53 g/g) was obtained with 50% DO.…”
Section: Resultssupporting
confidence: 55%
“…Earlier works demonstrated that in Bt cultures oxygen uptake rates are very high during the vegetative growth, falling drastically after the beginning of the transition phase and maintaining a decreasing profile until the end (Rowe et al 2003;Yezza et al 2005;Berbert-Molina et al 2008;Amicarelli et al 2010). Indeed, some authors verified that lower aeration rates in the sporulation phase, in relation to those employed in the earlier stages of growth, led to a greater toxicity in Btk cultures (Ghribi et al 2007a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations